Diseño de una colección de chaquetas formales en denim, empleando técnicas de confección de sastrería - Oña Marfetan, Lizeth Carina (2024)
The thesis titled “Design of a collection of formal denim jackets, using tailoring techniques” arises from the analysis of deficiency and loss of construction techniques in the production of tailored garments. Therefore, this work aims to revalue this art in a traditional way by implementing a new method of textile intervention through the collaboration of “EL GABAN SASTRERIA”. Through the analysis of the techniques and methods of tailoring, it is possible to propose innovative clothing in design, textile material and supplies. The work will be carried out in a chronological order that consists of: problem statement, bibliographic research, context analysis, research methodologies and finally the planning and development of the design proposal. Based on the analysis of the focus group that was developed with different artisan tailors in the city of Quito, they stated that this proposal could not be carried out without first analyzing techniques and washing processes for the use of denim and mainly they all agree that This textile must be processed before its production since, as they are formal garments, they should not lose their aesthetics and unique design. The results that were obtained through the sample calculation and analysis of the client establish that the target audience is men and women between 25 and 35 years of age, and they also make known their taste for good dressing and elegance, especially if your profession is based on formal aspects and high levels of seriousness. Which will allow total acceptance of the product since by providing comfort it is also part of the quality and formality standards